Analisis Kesalahan Siswa Introver dan Ekstrover Berdasarkan Kriteria Newman dalam Menyelesaikan Soal Cerita Materi Program Linear - Rosidah; Ilham Minggi; Syafirah Audiwinanda (Issues in Mathematics Education (IMED), 2022)
This study aims to describe the errors of introverted and extroverted students and the causes of their errors based on Newman's criteria in solving linear programming problems. The type of research used is descriptive qualitative research. There are 4 research subjects, namely 2 students with an introverted personality type and 2 students with an extroverted personality type. The research consisted of 2 students with an introverted personality type and 2 students with an extroverted personality type. Data collection techniques used are questionnaires, test questions, and interviews. The instruments used in data collection were personality type questionnaires, linear program material tests and interview guidelines. Data analysis techniques include data condensation, data presentation and drawing conclusions. The results showed that introverted students transformation error, process skills error and enconding error. Meanwhile, extroverted students make are reading error, comprehension error, transformation error, process skills error and enconding error. The causes of introverted students' errors based on the Newman procedure are wrong habits that are not corrected by the teacher, the principle of students not writing down non-negative constraints, feeling pressured because they are limited by time in doing questions. While the causes of extroverted students' errors are extroverted students who tend to be in a hurry in solving problems, cannot connect information to questions, do not master the prerequisite material and do not re-check the results of their answers.